Crimen organizado y su tipificacion en el contexto de la expansión del Derecho Penal (Revista de Derecho, 2013)
DOI: http://dx.doi.org/10.5377/derecho.v0i12.1005 Revista de Derecho No.12 2009 pp.133-158